An evaluation of the genus Kincaidiana Altman, 1936, with the designation of Altmanella n. gen. (Annelida, Clitellata, Lumbriculidae) - Fend, Steven V. (Zootaxa, 2009)
A review of morphological characters for the western Nearctic genus Kincaidiana indicated that the two described species should be assigned to separate genera. Kincaidiana freidris Cook was transferred to a new genus, Altmanella. New material resembling A. freidris was obtained from many sites throughout western North America. Morphology of the male reproductive structures varied among populations, and the most distinctive morphological differences were accounted for by splitting the taxon into two species, which roughly corresponded to large scale regional patterns. Typical A. freidris occurred in several Pacific Coast drainages. Altmanella idahoensis n. sp., mostly associated with the Snake River drainage, was distinguished from A. freidris by shorter and less muscular atria and penial structures. A second new lumbriculid species with the same basic arrangement of reproductive organs was collected in southeastern North America, and was provisionally assigned to Altmanella. However, in contrast to the petiolate atria and large penial structures of A. freidris and A. idahoensis, Altmanella lenati n. sp. has tubular atria and simple male porophores.